(untitled) (International Journal of Nursing Education, 2026)
Rapid digital transformation across industries has accelerated the adoption of advanced technologies to reduce manual workload, enhance efficiency, and optimize operational costs. Healthcare is undergoing a similar transformation, with artificial intelligence (AI) emerging as a key enabler of innovative care delivery models. Among these, Voice-Enabled Virtual Nursing Assistants (VNAs) represent a promising solution to address increasing care demands, workforce shortages, and rising healthcare costs. Virtual Nursing Assistants offer 24/7 availability, enabling continuous patient engagement beyond the limitations of human staffing. They assist patients by responding to health-related queries, providing medication reminders, monitoring symptoms, supporting chronic disease management, and offering emotional and mental health support. Evidence suggests that VNAs improve accuracy, timeliness, and accessibility of care compared to traditional methods. From a healthcare provider perspective, VNAs streamline documentation, support preliminary assessment and triage, enhance real-time monitoring, and optimize workflow efficiency. In critical care settings, the integration of virtual nursing roles has been identified as a viable approach to mitigating projected nursing workforce gaps while maintaining care quality. Additionally, VNAs demonstrate potential in education and staff development through virtual teaching platforms and cognitive learning enhancement. Future advancements are expected to expand VNA capabilities through wearable integration, electronic health record synchronization, advanced personalization, and diagnostic support. Despite challenges related to data security, ethics, cost, usability, and regulatory frameworks, Virtual Nursing Assistants represent a transformative digital health innovation with significant potential to improve patient outcomes, empowers especially elderly patients and reduces nurse’s workload, and strengthen healthcare systems.